Antinutritional Factors of some Wild Edible Fruits from Kolhapur District - S.R. Valvi, V.S. Rathod and (Recent Research in Science and Technology, 2011)
Total 8 wild edible fruits were studied for their antinutrional factors viz. Ficus racemosa L., Elaeagnus conferta Roxb. Flacourtia indica (Burm. f.) Merr., Glycosmis pentaphylla (Retz.) DC., Ziziphus rugosa Lamk., Meyna laxiflora Robyns., Cordia dichotoma Linn., Grewia tiliifolia Vahl. etc. The highest level of phytate were present in Ficus racemosa.,Ã‚Â  Glycosmis pentaphylla shows the highest level of oxalic acid and tannin is higher in Flacourtia indica where as saponin is rich in Meyna laxiflora.